From deposits to social practices: Integrated micromorphological analysis of floor sequences at Middle Bronze Age Erimi-Laonin tou Porakou, Cyprus. (October 2018) - Amadio, Marialucia
Abstract: Floors are a key data-set of cultural evidence in archaeological contexts as they offer potential for detecting and interpreting the spatial conventions through which economic and social relationships are represented and negotiated during the life-history of buildings and settlements. In this study, floor sequences from the Middle Bronze Age site of Erimi- Laonin tou Porakou (c. 1950–1650 BCE) have been analysed through an interdisciplinary approach based on integration of stratigraphic, micromorphological, spectroscopic (FTIR) and geochemical (XRF) analyses. This integrated approach is aimed at examining materials and technology in floor plaster manufacture as well as the impact of environment and activities on floor surfaces as indicators of continuity and change in use of space and related socio-cultural and economic implications. The multi-scalar data-set provided an effective framework with which to reconstruct every-day practices in the construction, use and maintenance of floor plasters within buildings. In particular, data analysed has permitted identification of the occurrence of specific recipes in floor plaster manufacture that suggest organisation of labour and production possibly at supra-household level. However, no clear evidence of pyrotechnological plasters has been recognised on the basis of data examined. Spatial and temporal changes in floor sequences reveal that floor plastering episodes represented important markers of building renovation during the life history of Erimi- Laonin tou Porakou . Instances were documented of the introduction of layers of new floor plaster types that corresponded to changes in activities within building, from dirtier to cleaner, and to enhancement of spatial and architectural elaboration of built space. The integrated micromorphological analysis applied to floor plaster sequences has provided new insights into the dynamic scenario of social organisation at Erimi- Loanin tou Porakou, contributing to delineation of a range of potential avenues for studying socio-cultural trajectories and evolutionary pathways of Bronze Age communities in Cyprus. Highlights: Integrated high-resolution analyses offer an apt data-set to study floor sequences. Floor plasters at Erimi-LtP were manufactured according to specific recipes. The production of plaster-types appears to have been at supra-household level. Plaster-floors contributed to definition of socio-cultural settings within buildings.